Experimental study on dynamic responses of a deep-sea mining system. (15th March 2022) - Wu, Qi; Yang, Jianmin; Guo, Xiaoxian; Liu, Lei; Lu, Wenyue; Lu, Haining
Abstract: The global demand for minerals has raised interest in the design and study of Deep-Sea Mining (DSM) systems for minerals. In this study, the global dynamic responses of a DSM system are investigated using a scaled model test in an ocean basin. Vessel movements, loads of rigid pipe, and buffer accelerations were recorded when the system is exposed to different excitation. The peak response amplitude operator of the roll motion of a vessel under a 90 ∘ incident wave is found to decrease by 26% due to the underwater structures of the DSM system. Under excitation containing irregular waves, the maximum response value occurs at 0.4 Hz in the y-axis moments under current only excitation and at 0.11 Hz in the axial force. The experiments give insight into the vessel-motion-induced vortex-induced vibration (VIV) on the rigid pipe, and find that the interaction of irregular waves and currents on the DSM system resulting in 48%, 25% and 37.8% increase of the buffer's displacements in x-, y- and z-direction compared with the linear combination of results under current only and wave only case. These results can be used to develop general guidelines for the design of DSM systems in the industry. Highlights: A complete deep sea mining system is modeled for the first time in an indoor laboratory with simulating irregular waves, sheer currents, and winds. The roll-RAO amplitude of the surface vessel under the 90° incident wave is decreased by 26% due the damping effect of the underwater parts. Three types of motion are found on the rigid pipe responses to the coupled wave–wind–current condition: the global response, vessel motion-induced VIV, and current induced VIV. The Weibull distribution fits well with the extreme-value distributions of lateral moments, whereas it would underestimate the top tension. The interaction between irregular waves and currents has a nonlinear effect on the DSM, and increases the buffer's displacements in the x, y, z directions.